2003
DOI: 10.1099/mic.0.25981-0
|View full text |Cite
|
Sign up to set email alerts
|

An inducible tellurite-resistance operon in Proteus mirabilis

Abstract: Tellurite resistance (Te r ) is widespread in nature and it is shown here that the natural resistance of Proteus mirabilis to tellurite is due to a chromosomally located orthologue of plasmid-borne ter genes found in enteric bacteria. The P. mirabilis ter locus (terZABCDE) was identified in a screen of Tn5lacZ-generated mutants of which one contained an insertion in terC. The P. mirabilis terC mutant displayed increased susceptibility to tellurite (Te s ) and complementation with terC carried on a multicopy pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 44 publications
1
40
1
Order By: Relevance
“…The real time PCR assay also confirmed that the ter gene cluster in E. coli KL53 and its regulatory region are not inducible by potassium tellurite and/or hydrogen peroxide (Vavrova et al 2006). This observation is in contrast to the regulation of the ter operon in the urinary pathogen Proteus mirabilis, in which transcription is induced by oxidative stress (Toptchieva et al 2003).…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…The real time PCR assay also confirmed that the ter gene cluster in E. coli KL53 and its regulatory region are not inducible by potassium tellurite and/or hydrogen peroxide (Vavrova et al 2006). This observation is in contrast to the regulation of the ter operon in the urinary pathogen Proteus mirabilis, in which transcription is induced by oxidative stress (Toptchieva et al 2003).…”
Section: Discussioncontrasting
confidence: 45%
“…Promoter strength was measured with a fluorimetric assay. GFPuv reporter was chosen because tellurite toxicity prevented the use of the lacZ fusion as a reporter for regulatory studies (Toptchieva et al 2003). E. coli BL21(DE3) containing pBAD-GFPuv with the araBAD promoter, PBAD, from the arabinose operon, and the corresponding regulatory gene, araC, were used as positive and negative controls for fluorimetry that were dependent on arabinose addition/non-addition to the growth medium, respectively.…”
Section: Fluorimetrymentioning
confidence: 99%
See 1 more Smart Citation
“…Toptchieva et al (2003) found that intrinsic tellurite toxicity prevented the use of the lacZ fusion as a reporter for regulatory studies in Proteus mirabilis. Since tellurite oxidizes thiol groups, it contributes to oxidative stress and might affect the b-galactosidase enzyme in a similar way as ROS.…”
Section: Upregulation Of Phra Expression Depends On Light Intensity Amentioning
confidence: 99%
“…PF02342), which are important for tellurite resistance. These proteins might be implicated in oxidative stress response for two reasons: (i) the toxicity of tellurite could be related to its oxidizing capacity (53,55) and (ii) the ter operon of Proteus mirabilis is induced by oxidative stress caused by H 2 O 2 or methyl viologen (54).…”
Section: Vol 187 2005mentioning
confidence: 99%